Effect of pre-stretching deformation treatment process on microstructure and mechanical properties of Al-Cu-Mg alloy. (June 2022) - Yu, Chunqi; Feng, Yicheng; Wang, Lei; Fu, Jinlai; Kang, Fuwei; Zhao, Sicong; Guo, Erjun; Ma, Baoxia
Abstract: Strength and plasticity are essential properties in Al-Cu-Mg alloy for the aerospace, automotive, and weapon industries. Both cold rolling and pre-deformation are critical practices to obtain high strength as well as high plasticity. In this study, the microstructure and properties of the Al-Cu-Mg alloy with various deformation treatments were studied by using optical microscope, scanning electron microscope, electron back scatter diffraction technique, transmission electron microscope, Vickers hardness tester, and tensile tester. The results show that the brittle T phases can cause stress concentration which is not conducive to the plasticity of the alloy. The tiny GPB zones distributed homogeneously can increase the ultimate tensile strength. There are fiber 001 < 110 > , Copper 112 < 111 > , Brass 011 < 211 > , S 123 < 634 > , Goss 011 < 100 > , Cube 001 < 100 > , and R 124 < 211 > texture components in the cold-rolled deformed 2324 aluminum alloy. Compared to cold-rolled deformed alloy, the fiber texture component disappears in the pre-stretched deformed alloy. The intensity of Brass and S texture components are helpful to obtaining higher strength of the alloy. The maximum ultimate tensile strength and yield strength are achieved in the alloy with the pre-stretching deformation of 1.4%, enhancing 42.7 MPa and 147.8 MPa compared to the cold-rolled deformed alloy, respectively. However, the elongation is decreased to 13.3% in the alloy with the pre-stretching deformation of 1.4%. Graphical Abstract: ga1 Highlights: Cold rolling and pre-stretching processes were evaluated for the Al-Cu-Mg alloys. Different deformation treatments were employed to enhance the mechanical behavior. Texture types had different effects on the properties of Al-Cu-Mg alloys.